Asosiasi Eksportir Kopi Indonesia (Aeki) Dalam Peran Dan Kepentingan Mendorong Ekspor Kopi Indonesia Ke Jepang 2018 - Rahayu, Muh Agus; Purwono, Andi (Faculty of Social and Political Sciences - Universitas Wahid Hasyim, 2022)
Coffee is one of the most popular drinks in the world. As one of the largest coffee producing countries in the world, of course Indonesia will improve and manage processed coffee, both in the form of production and market share. In connection with the increase in coffee lovers in the country of Sakura (Japan) and also bilateral relations that have existed for a very long time, Indonesia has made Japan a destination for Indonesian coffee exports, through a Non-Government Organization or non-governmental organization that oversees the coffee industry called the Association of Exporters and Industries. Indonesian Coffee (AEKI), farmers and entrepreneurs as well as Indonesian coffee industry players who are members of the AEKI membership want to encourage the Indonesian government to export coffee to Japan as an effort to improve the National Economy. The state economy will be strong if the individual economy is also strong, this is as stated by Andrew Moravcsik, the state exists as a forum for individuals who become community groups.